Association between High-Risk Pregnancy History and High-Efficacy Postpartum Contraception Use in North Carolina - Maya E. Cox-Terry; Elizabeth D. Enright; Godwin Y. Dogbey; James M. Edwards (Maternal and Child Health Journal, 2026)
Abstract Objective To evaluate factors associated with postpartum use of high-efficacy contraception among postpartum individuals in North Carolina and to assess whether a history of high-risk pregnancy was associated with increased use of WHO Tier 1 contraceptive methods. Study Design North Carolina Pregnancy Risk Assessment Monitoring System (PRAMS) data from 2012 to 2020 were analyzed. The analytic sample included 6,993 postpartum respondents. A composite high-risk pregnancy history index was created using self-reported and birth certificate variables including preterm birth, low birth weight, obesity, hypertension, diabetes, depression, and inadequate prenatal care. Multivariable logistic regression was used to evaluate factors associated with postpartum use of WHO Tier 1 contraception. Results A cumulative sample of 13,866 postpartum persons were selected and invited to complete the survey; 6,993 responded and were considered participants. History of high-risk pregnancy was associated with slightly increased odds of postpartum Tier 1 contraception use (aOR 1.18, 95% CI 1.00–1.39, p < 0.05), although the association was modest. Other significant factors associated with high-efficacy contraception use included multiparity (aOR = 2.00, 95% CI 1.70 to 2.36), planned conception (aOR = 0.72, 95% CI 0.62 to 0.85), living infant (aOR = 2.85, 95%CI 1.42 to 5.72), postpartum contraception counseling (aOR = 0.36, 95% CI 0.28 to 0.45), postpartum depression screening (aOR = 1.40, 95% CI 1.05 to 1.89), Black and Asian races (aOR = 0.78, 95% CI 0.64 to 0.95 and aOR = 0.36, 95% CI 0.23 to 0.59, respectively), a bachelor’s or master’s degree (aOR = 0.64, 95% CI 0.50 to 0.82 and aOR = 0.66, 95% CI 0.48 to 0.89, respectively), and age groups 30–34 and 35–39 year-olds (aOR = 1.31, 95% CI 1.08 to 1.59 and aOR = 1.50, 95% CI 1.19 to 1.89, respectively). Conclusion In this North Carolina population, high-risk pregnancy history was only modestly associated with postpartum use of high-efficacy contraception. Other findings of this study suggest that high efficacy postpartum contraception use is influenced by demographic, reproductive, and healthcare interaction factors beyond pregnancy risk status alone. Interventions focused on equitable, patient-centered counseling and access to postpartum contraception may improve reproductive planning among patients with high-risk pregnancies who desire pregnancy spacing or prevention.